Examination of Combustion-Generated Smoke Particles from Biomass at Source: Relation to Atmospheric Light Absorption. Issue 1 (2nd January 2020) - Jones, Jenny; Mitchell, Edward; Williams, Alan; Kumi-Barimah, E; Jose, Gin; Bartle, Keith; Hondow, Nicole; Lea-Langton, Amanda
ABSTRACT: The formation of carbonaceous aerosols from biomass combustion is associated with a high degree of uncertainty in global climate models. In this work, soot samples were generated from the combustion of pine wood, wheat straw and barley straw in a fixed bed stove; as well as from the combustion of biomass pyrolysis model compounds. Samples were collected on filters, which were used for the determination of Absorption Angstrom Exponent (AAE). In addition, the content and composition of elemental carbon (EC) and organic carbon (OC) were determined, and the interrelationships between these and the AAE were examined. It was found that the spectroscopic signature of samples with high 'brown carbon' emissions was comparable to that of many PAH and polyphenols, with AAE ranging from 1.0–1.2 for model compounds to 0.5–5.7 for biomass. In addition to the filter samples, particles were collected directly onto microscopy grids and analysed by transmission electron microscopy – electron energy loss spectroscopy (TEM-EELS) in order to determine structural characteristics. This was used to examine the impact of combustion conditions and flue gas dilution on particle structure. Smouldering phase and diluted particles were found to be less graphitic and twice as oxygenated as undiluted flaming phase particles. The results are interpreted to better understand the impact of combustion processes on soot formation from biomass combustion. Abbreviations: AAE: absorption angstrom exponent; ATN: light attenuation; AToFMS: aerosol time of flight mass spectrometer; BC: black carbon; BrC: brown carbon; C:O: carbon to oxygen ratio; CPD: cyclopentadienyl radical C5H5; DMS: differential mobility spectrometer; EC: elemental carbon; EELS: electron energy loss spectroscopy; HACA: hydrogen abstraction carbon addition; MCE: modified combustion efficiency; OA: organic aerosols; OC: organic carbon; PM: particulate matter; POM: primary (particulate)organic matter; Py-GC/MS: pyrolysis gas chromatography/mass spectrometry; sp2: amount of sp2 orbital hybridisation in atomic structure; SSA: single scattering albedo; TC: total carbon (BC+OC) or (EC+OC); TEM: transmission electron microscope; TGA: thermogravimetric analysis